A threatening exchange: gender and life history strategy predict perceptions and reasoning about sexual harassment - Dillon, Haley Moss; Adair, Lora E.; Brase, Gary L. (My University, 2015)
Sexual harassment is a serious societal issue, with extensive economic and psychological consequences, yet it is also an ill-defined construct fundamentally defined in terms of subjective perception. The current work was designed to examine the ways in which individual differences between people are systematically related to different perceptions of sexual harassment scenarios, as well as reasoning about those harassment situations. Participants (N = 460) read several possible harassment scenarios and rated how uncomfortable they would find them. They then also evaluated a quid pro quo sexual harassment situation in terms of their interpretation of it as a threat or a social exchange and completed a deductive reasoning task about the same situation. Females and individuals with slow life history strategies were more uncomfortable with potential harassment situations and were more likely to interpret the quid pro quo scenario as a threat. Further, interpreting the scenario as a threat was associated with poorer performance on the deductive logic task, compared to those who interpreted the scenario as a social exchange.
Keywords: Sexual harassment; Decision making; Social exchange; Threats; Human reasoning